Collaboration within the context of the Healthy School Approach (HSA): The case of a disadvantaged elementary school in Quebec - Rivard, Marie-Claude; Deslandes, Rollande; Beaudoin, Charlotte (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
This case study focuses on the groundwork aiming at developing school-family-community collaboration in the deployment of the HSA in a low socio-economic status elementary school. Two theoretical models - the HSA and Hoover-Dempsey et al. (1997, 2010) models - guided the analysis of five discussion groups (N=31) regarding their perceptions of the place of health in school and of parents' and educators' health related practices to support HSA deployment and to establish the pathway to a better school-family-community collaboration. The school is committed to health despite its low economic status. Encouragement, modeling and teaching are the perceived practices or actions. Keywords: healthy school, perceptions, practices, collaboration, stakeholders.